Effect of protective release coatings on the basis of superdispersersed zirconium oxide powder on the formation of gas defects in bronze casting; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Martyushev N. V. Nikita Vladimirovich (2014, 2014)
Title screen